The Legal Ramifications of Sexual Commodification in Trademark Usage in Indonesia - Rory Jeff Akyuwen; Muchtar Anshary Hamid Labetubun; Senly Soplantila (Faculty of Law, Sriwijaya University, Indonesia, 2024)
The ownership of trademark rights is a fundamental component of industrial property rights within the broader spectrum of intellectual property law. Law Number 20 of 2016 concerning Marks and Geographical Indications, specifically Article 20, mandates that brand naming must not contravene state ideology, statutory regulations, religious morality, decency, or public order. This study seeks to critically examine and analyse trademarks deemed inappropriate because they violate existing legislative provisions. Certain trademarks utilised by business entities infringe upon societal standards of decency by engaging in sexual commodification. The research adopts a juridical-normative methodology, incorporating both legislative and conceptual frameworks. The legal materials examined include primary, secondary, and tertiary sources, which are qualitatively analysed to address the research questions. The findings reveal that sexual commodification in trademark naming, characterised by the exploitation of pornography, violates religious norms and societal decency. Therefore, such trademarks are not eligible for registration. Furthermore, any trademarks that have been registered and are found to contain elements of sexual commodification may be subject to revocation, as they conflict with state ideology, legislation, religious morality, decency, and public order.